2017
DOI: 10.3892/etm.2017.4907
|View full text |Cite
|
Sign up to set email alerts
|

Screening of differentially expressed genes associated with Kawasaki disease by microarray analysis

Abstract: Abstract. Kawasaki disease (KD) is an autoimmune disorder that can induce coronary artery aneurysms, particularly in the case of delayed diagnosis and/or treatment. Early diagnosis is important for treatment and reduces the risk of heart injury. The aim of the present study was to identify differentially expressed genes by comparing the levels of gene expression in human umbilical vein endothelial cells following treatment with plasma from healthy individuals and patients with acute or convalescent KD. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although there were a number of differentially regulated targets, autoantibodies to EDIL3 were most clearly overexpressed in Kawasaki disease patients as compared to MIS-C ( Figure 7 H). The gene encoding this protein has previously been associated with Kawasaki disease ( Jiang et al., 2017 ), and the target protein is a structural glycoprotein in arterial vessel walls that is regulated in response to vascular injury. One function of EDIL3 is to inhibit inflammatory cell recruitment and extravasation across the endothelium, and when EDIL3 is disrupted in mice, there is increased tissue infiltration of neutrophils and elevated inflammatory responses ( Choi et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there were a number of differentially regulated targets, autoantibodies to EDIL3 were most clearly overexpressed in Kawasaki disease patients as compared to MIS-C ( Figure 7 H). The gene encoding this protein has previously been associated with Kawasaki disease ( Jiang et al., 2017 ), and the target protein is a structural glycoprotein in arterial vessel walls that is regulated in response to vascular injury. One function of EDIL3 is to inhibit inflammatory cell recruitment and extravasation across the endothelium, and when EDIL3 is disrupted in mice, there is increased tissue infiltration of neutrophils and elevated inflammatory responses ( Choi et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…The present study also predicted that the selected miRNAs may be involved in KD by regulating the inflammatory target genes expressed in PBMCs. CXCR1 was one of the targets and previous studies have reported that IL-8 and its receptors, CXCR1 and C-X-C chemokine receptor type 2, were upregulated in patients with KD ( 46 ) and in coronary artery diseases ( 47 ). By binding to CXCR1, IL-8 may promote the production of other inflammatory mediators through the activation of the p38-mitogen-activated protein kinase/extracellular signal-regulated kinase-nuclear factor (NF)-κB pathways ( 48 ), which may subsequently induce apoptosis in vascular endothelial cells, a potential mechanism for KD ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various microarray based studies have been carried out to identify the genes associated with KD. Expression of these genes may be used as a novel diagnostic and prognostic biomarker for KD [51].…”
Section: Biomarkers In Kdmentioning
confidence: 99%